Analisis Indeks Pembangunan Manusia Yang Berpengaruh Terhadap Tingkat Kemiskinan Di Provinsi Banten - Desmawan, Deris; Valentino, Dikie; Kusuma, Ferdiyana Indra; M, M. Fajar; Ardani, Novi; Sumarni, Pipin (Universitas Labuhanbatu, 2023)
The Human Development Index (HDI) and poverty level are two important aspects of economic development that are interrelated. HDI is a benchmark used to assess the level of welfare of the population of a region, while the poverty rate indicates the number of individuals living below the poverty line. The purpose of this research is to examine the impact of the Human Development Index on the poverty rate in Banten Province.